Intramural neurofibroma of the trachea treated by multiple stents - Cranshaw, J (BMJ Group, 2001)
The case history is presented of a patient in whom an intramural tracheal neurofibroma developed, causing severe airway stenosis. The patient was treated with multiple stents over a period of 5 years because of progression of the disease and associated airflow limitation. Clinicians should be aware of this rare complication of neurofibromatosis.